Obesity is a communicable disease - Sanjay Kalra; Madhur Verma; Nitin Kapoor (Journal of the Pakistan Medical Association, 2024)
Obesity has multiple causes and correlates. Usually studied as a metabolic and endocrine disease, with mechanical and musculoskeletal comorbidities, obesity also has a communicable angle to it. Obesity can be considered a communicable disease from the conventional point of view, as it is associated with viral etiology in animal and human models. It is also associated with increased prevalence and worse prognosis of infectious diseases. Not only that, obesity is a ‘socially communicable’ disease, as it ‘spreads’ amongst people living in similar environments. Keywords: Communicable disease, infectious disease, obesity, overweight, public health